Comparison of Veterinary Nutrition Exam Results After Classroom or Virtual Teaching During the COVID-19 Pandemic at a German University - Böswald, Linda F.; Pankratz, Christina; Dobenecker, Britta; Herbst, Sarah; Klein, Carmen; Alf, Vanessa; Kienzle, Ellen (Frontiers in Animal Science, 2022)
Due to the COVID-19 pandemic, university teaching had to be kept up in spite of severe contact restrictions. Virtual teaching of animal nutrition was implemented at the Veterinary Faculty of the Ludwig-Maximilians-Universität (LMU) München, Germany, for both lectures and practical courses. Live online classes were held via Zoom®, and recordings were accessible afterwards. Animal nutrition is taught in the 5th and 6th term of the veterinary studies, followed by an oral state exam about subjects from both terms. In this study, the success of classroom vs. virtual teaching in veterinary animal nutrition was evaluated by comparison of exam results. Two exam cohorts (2019, before the pandemic; 2020, with one term of virtual teaching during the pandemic) were evaluated. The results indicated no significant difference of teaching method on the grades. However, there was a significantly higher probability of students not taking or failing the exam in the 2020 exam cohort, suggesting a general effect of the pandemic on the students. Additionally, two surveys were distributed among the students during summer term 2020 and winter term 2020/21, when virtual teaching due to the pandemic had been implemented for the first time. The survey results provide insights into the students´ view of benefits and problems of virtual teaching in animal nutrition at the LMU. The majority was in favor of the live online format for lectures and courses in computed-based ration calculation, whilst feedstuff demonstrations were preferred in classroom setting.